Tekanan Industri Rokok terhadap upaya Indonesia dalam meratifikasi Konvensi pengendalian Tembakau sejak tahun 2003. - Rina Ayu Panca Rini (HI 13 UMY 295, 2013)
This research aims to know the efforts made by industry smoking in pursing ratification of the Framework Convention on Tobacco Control (FCTC) in 2003 conducted by Indonesia. Subjects in the research industry is developing in Indonesia smoking good multinational cigarette companies and cigarette companies nationwide. The technique of writing a thesis with the methods deductively. While data collection is done by collecting various authors data of secondary literature on a daily basis is good and relevant. The conclusions obtained in writing this is that checking them Framework Convention on Tobacco Control (FCTC) in 2003 done by Indonesia was also accompanied various business of the tobacco industry to hinder ratification through the lobby, campaign economy, and the implementation of CSR . Keywords: FCTC, ratification, Indonesia, tobacco industry.